Angiodysplasia and ileal carcinoid. Issue 11 (November 1991) - Mac Mahon, M; Courtney, M G; Doyle, J S; Leader, M
Abstract : A case of angiodysplasia, symptomatic for 18 years, is presented. This case highlights the difficulty of establishing a diagnosis. Associated findings included aortic stenosis and a carcinoid tumour of the ileum. Despite transfusion of a total of 1200 units of blood the liver was normal at necropsy.